Avtorice v slovenskih srednješolskih berilih - Božič, Zoran (Jezik in slovstvo, 2017)
The paper is based on quantitative research on the share of women authors in Slovenian secondary school literature textbooks between 1850 and 2000. The highest share (about 15%) was achieved by women authors after the Second World War and in contemporary textbooks. However, this share occurred in only one of three competing books, which offers a considerably larger selection of authors than required by the curriculum. The research showed that the share of women authors depends on the scope of the approach: the fewer authors included, the smaller the chance of women authors being represented. With a very strict selection of nationally representative authors, the female gender is not represented at all. The gender of the selector(s) may influence the inclusion of women authors, but not necessarily: even if a textbook's editor is a woman, she may still fail to include a single woman author. A comparison between textbooks and literary-historical selections shows that women authors in textbooks are less represented (due to limitations of the scope, as determined by the included literary texts), and that selection criteria may also differ.d
Keywords: avtorice; pisateljice; slovenska srednješolska berila; literarna zgodovina; history of literature; didaktika književnosti; kanonizacija; srednješolski učbeniki